STUDY OF MANGANESE MN(II) BIOOXIDATION USING BACTERIA: A COMPREHENSIVE REVIEW - Sumito, Timotius
Manganese is an element ranked 12th by abundance in the earth’s crust. It is also the second most abundant transition metal next to iron. Manganese can be used as metals for steelmaking or as its oxides (MnO2) for many applications, such as battery materials, glass colourant, etc. Currently, the oxidation of Mn(II) to MnO2 are done by electrolysis to produce electrolytic manganese dioxide (EMD) or chemical method to produce chemical manganese dioxide (CMD). Both methods are energy intensive because the process is carried out at high temperature. Also, the use of organic acid as the reductor has become trends in manganese leaching, but its residue will decrease the efficiency of electrolysis or chemical oxidation. Microorganism, especially bacteria, are known involved in manganese cycle and having the ability to oxidize Mn(II) to MnO2. Based on the fact, this comprehensive review is expected to give an insight about manganese biooxidation as an alternative method to produce MnO2 and the factors affecting manganese biooxidation. Several references are collected to provide information about manganese production, uses, electrolysis and chemical methods for MnO2 synthesis, MnO2 polymorphism, mechanism of manganese biooxidation by bacteria, and some manganese biooxidation researches. Biooxidation research by bacteria in this review includes Leptothrix dischopora, Bacillus sp., Pseudomonas putida, Citrobacter freundii, Lysinibacillus sp., Stenotrophomonas sp., Serratia marcescens, and Shewanella sp., it should be noted that manganese biooxidation research by now are focused for biogeochemical, microbiology, or environmental application. Factors affecting biooxidation are discussed after those published researches are reviewed. The result of this review shows that manganese biooxidation can occur enzymatically (involving enzymes) or non-enzymatically (only modifications of solution potential and pH). Factors affecting manganese biooxidation are dissolved oxygen concentration, pH, addition of another metal’s cation, manganese concentration, and temperature. As dissolved oxygen rises, biooxidation will occurs faster. Oxygen consumption occurs according to stoichiometry of Mn2+ + ½ O2 ? MnO2 + 2H+. The optimal pH value is ranged at 7-7,5. If pH is too low, Mn2+ stability is high. If pH is too high, there will be autocatalytic effects but the oxidation yields are relatively low. Metal cations known to increase yield in manganese biooxidation are Ca2+ and Cu2+. Temperature is optimum at 25-50 ?C. At temperature below or higher, manganese oxidation activity will deteriorate.